THE EFFECT OF CONSUMING NIKE FISH ON BLOOD URIC ACID LEVELS OF UNIVERSITY BINA MANDIRI GORONTALO EMPLOYEES - Warastuti, Rita Amini; Lamusu, Sri Rahayu (International Journal of Health Science & Medical Research, 2024)
Nike fish (duwo, family Gobiidae) is unique because of its periodic appearance so it is eagerly awaited and consumed in large quantities. Based on the family similarities between Nike and Anchovy, it can be estimated that the purine in Nike is quite high (purine in Anchovy is 411 mg/100g). Consuming large amounts of Nike, especially in groups recommended for a low-purine diet (100-150 mg purine/day), can impact high uric acid levels in the blood and lead to the emergence of Gout Arthritis. This research aimed to determine the effect of consuming Nike on uric acid levels of University Bina Mandiri (UBMG) employees. This research is the quantitative experimental type of research, which was carried out to determine the effect of consuming Nike fish on uric acid levels before and after. Data was collected from 31 employees through interviews and measuring uric acid levels before and after giving Nike. The study's results found an increase in uric acid levels before and after the intervention of 5.7 mg/dl and 6.2 mg/dl. Statistical analysis of the ANOVA test obtained a P value or significance before treatment of 0.003, and after treatment of 0.002 or a probability value of 0.05; the research conclusion is that giving Nike had a significant effect on the uric acid levels of employees at UBMG.Keywords: Consuming; Nike fish; Uric acid level.